Neutralized Nanoparticle Composed of SS‐Cleavable and pH‐Activated Lipid‐Like Material as a Long‐Lasting and Liver‐Specific Gene Delivery System. Issue 8 (26th March 2014) - Ukawa, Masami; Akita, Hidetaka; Hayashi, Yasuhiro; Ishiba, Ryohei; Tange, Kota; Arai, Masaya; Kubo, Kazuhiro; Higuchi, Yuriko; Shimizu, Kazunori; Konishi, Satoshi; Hashida, Mitsuru; Harashima, Hideyoshi
<x xml:space="preserve">Abstract</x> Charge‐neutralized lipid envelope‐type nanoparticles formed with SS‐cleavable and pH‐activated lipid‐like materials (ssPalm) accumulate rapidly in the liver without forming aggregates in the blood circulation, and result in a liver‐specific gene expression for a long duration (>2 weeks) with neither immunological responses nor hepatotoxicity after intraveneous administration, when it carries pDNA free from CpG‐motifs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>